Integrating Environmental Costs into the Life Cycle Costing and Acquisition Strategy of Assets: Array - Baloyi, Wiston Mbhazima (The Journal of Accounting and Management, 2021)
Objective: The aim of this paper is to integrate environmental costs into the life cycle costing and acquisition strategy of assets of the firm. Prior Work: Literature reveals that effective life cycle costing of assets and life cycle assessment are fundamental to the attainment of the firm’s long-term goals, which, in turn, enhances firm’s performance. Furthermore, life cycle costing has been regarded as a useful tool for improving capital investments of assets. Approach: The paper follows a normative research approach. The paper illustrates the existing life cycle costing approach and describes the way in which environmental costs can be integrated to broaden the cost base while taking cognisance of the environmental impact. Implications: When acquiring assets and in reporting, decision-makers and policy-designers can integrate environmental costs in the life cycle costing of assets. Value: This paper intends to fill gap in the body of knowledge in the field of environmental sustainability. The paper is unique in that it proposes a life cycle cost assessment framework and expounds the importance of integrating environmental costs into life cycle costing and the asset acquisition strategy. The paper makes a number of recommendations.